Opioid Prescribing After Opioid-related Inpatient Hospitalizations by Diagnosis: A Cohort Study. Issue 10 (October 2019) - Lagisetty, Pooja A.; Lin, Lewei A.; Ganoczy, Dara; Haffajee, Rebecca L.; Iwashyna, Theodore J.; Bohnert, Amy S.B.
Abstract : Background: Any opioid-related hospitalization is an indicator of opioid-related harm and should ideally trigger carefully monitored decreases in opioid prescribing after inpatient stays in many, if not most, cases. However, past studies on opioid prescribing after hospitalizations have largely been limited to overdose related visits. It is unclear whether prescribing is different for other opioid-related indications such as opioid dependence and abuse and how that may compare with hospitalizations for overdose. Objective: To examine opioid-prescribing patterns before and after opioid-related hospitalizations for all opioid-related indications, not limited to overdose. Research Design: Retrospective cohort analysis of Veterans Health Administration (VHA) administrative claims from 2011 to 2014. Subjects: VHA patients who were hospitalized between fiscal years 2011 and 2014 and had at least 1 prescription opioid medication filled through the VHA pharmacy before their hospitalization. Measures: Opioid dispensing trajectories after hospitalization by opioid-related indication (ie, opioid dependence and/or abuse vs. overdose) compared with prescribing patterns for non–opioid-related hospitalizations. Results: Overall, opioid dosage dropped significantly (66% for dependence/abuse, 42% for overdose, and 3% for nonopioid diagnoses; P <0.001) across all 3 categories when comparing dose 57–63 days after admission to 57–63 days before hospitalization. However, 47% of the patients remained on the same dose or increased their opioid dose at 60 days after an opioid-related hospitalization. After adjusting for covariates, patients with a primary diagnosis of dependence/abuse had higher odds of having their dose discontinued compared with those with overdose: odds ratio (OR) 2.17 (1.19–3.96). Patients with admissions for opioid dependence and/or abuse had a statistically significant higher prevalence of depression, posttraumatic stress disorder, anxiety, and substance use disorders compared with those with an opioid overdose hospitalization. Conclusions: Opioid prescribing and patient risk factors before and after opioid-related hospitalizations vary by indication for hospitalization. To reduce costs and morbidity associated with opioid-related hospitalizations, opioid deintensification efforts need to be tailored to indication for hospitalization. Abstract : Supplemental Digital Content is available in the text.